إدراك طلاب كلية التمريض في جامعة تشرين لحقوق المريض - طويل, علاء; اصبيره, ولاء (Latakia University Journal -Medical Sciences Series, 2018)
هدف هذا البحث إلى تحديد إدراك طلاب كلية التمريض في جامعة تشرين لحقوق المريض. من خلال عينة طبقية مؤلفة من 750 طالب/ة من كلية التمريض من العام الدراسي 2017-2018 في السنوات الدراسية الثانية والثالثة والرابعة, من أهم النتائج التي أظهرها البحث: بشكل عام إن عينة البحث من طلاب كلية التمريض كانوا غير متأكدين من إدراكهم لحقوق المريض, وأن إدراك طلاب السنة الرابعة لحقوق المريض حقق النسبة الأعلى بين السنوات يليهم طلاب السنة الثالثة ثم طلاب السنة الثانية. The study aimed to identify the students'perception of the Faculty of Nursing at Tishreen University for patient rights. Through stratified sample consisted of 750 students from the Faculty of Nursing for the academic year 2017-2018 in the second, third and fourth years. The most important results of the study: Overall, the research sample of nursing students was unsure of their perception of the patients' rights, and that the fourth year students' perception of the patients' rights achieved the highest percentage among years followed by third year students and second year students